Perfect little lives - Brown, Amber; Brown, Danielle Nicole (Graydon House, 2023)
With her past set on haunting her, Simone, whose father was convicted of murdering her mother ten years ago, finds a chance encounter with her childhood next-door neighbor revealing a shocking secret that could prove her father's innocence or destroy her carefully rebuilt life.